Marianne's liberty in jeopardy? A French analysis on recent counterterrorism legal developments - De Massol De Rebetz, Roxane; Van Der Woude, Maartje (Critical studies on terrorism, 2020)
This article analyses two recent French counterterrorist legislations (Law No. 2016-386 - hereafter OCT&F law and the Law No 2017-1510 - hereafter the OCT&Flaw) through the lens of distinct yet complementary theoretical frameworks. Combining the State of Exception thesis of Giorgio Agamben, the Enemy Penology as framed by Günther Jakobs as well as the more recent scholarship contributions on Pre-Crime, the article seeks to contribute to the scholarly debate on the use and the consequences of the use of criminal and administrative law in the fight against terrorism. In view of the numerous terrorist attacks that France has faced in recent years, the article aims to provide deeper knowledge of the French case by drawing substantially from the unfamiliar French scholarship. The article argues that the measures recently adopted seem to deepen the exceptional and pre-emptive logic in which potentially dangerous subjects have to be identified as "the enemy" as soon as possible in order to then be contained and dealt with.